-3(-1x+6)=-15

Simple and best practice solution for -3(-1x+6)=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-1x+6)=-15 equation:


Simplifying
-3(-1x + 6) = -15

Reorder the terms:
-3(6 + -1x) = -15
(6 * -3 + -1x * -3) = -15
(-18 + 3x) = -15

Solving
-18 + 3x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 3x = -15 + 18

Combine like terms: -18 + 18 = 0
0 + 3x = -15 + 18
3x = -15 + 18

Combine like terms: -15 + 18 = 3
3x = 3

Divide each side by '3'.
x = 1

Simplifying
x = 1

See similar equations:

| 300=12x+9 | | 5x+7+30=-8+3x | | y=2abs(x+1) | | 2.68d+2.04=1.02+6.1 | | (4y+26)(3x-5)= | | 7-15=3x+1 | | 9x+25=2x+6 | | 3+2(3n+2)=-41 | | .5x+3=.75x-7.75 | | 12(x)+9=300 | | 41k+11=16 | | 5=7+2x | | 12x+(7-x)2= | | x/3=2/9 | | 2(x+10)=4(x-2) | | -8(4+9x)=3(x-1) | | 25t+30b=750 | | 3x+1=1-3x | | -60+40x=20x | | (t)+2.7=4.5 | | -7(y-2)=-2y+39 | | 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 |

Equations solver categories